2014
DOI: 10.1111/jmwh.12175
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Midwives to Serve as Preceptors: An American College of Nurse‐Midwives Survey

Abstract: There is a strong commitment from preceptors to give back to the profession through the teaching of the future generation of midwives. Many of the barriers to precepting could be addressed by ACNM, the Accreditation Commission for Midwifery Education, and individual midwifery education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 20 publications
(24 reference statements)
5
48
0
Order By: Relevance
“…For those who taught student nurse-midwives, it occupied less than a quarter of their time with compensation received by fewer than half. Lack of payment was not identified as a barrier to precepting nurse-midwifery students, consistent with other research (Germano, Schorn, Phillippi, & Schuiling, 2014).…”
Section: Aim 1 Nature and Scope Of The Practice Environmentsupporting
confidence: 89%
“…For those who taught student nurse-midwives, it occupied less than a quarter of their time with compensation received by fewer than half. Lack of payment was not identified as a barrier to precepting nurse-midwifery students, consistent with other research (Germano, Schorn, Phillippi, & Schuiling, 2014).…”
Section: Aim 1 Nature and Scope Of The Practice Environmentsupporting
confidence: 89%
“…Between 2000 and 2014, US nurse‐midwifery education programs increased the number of new graduates by 25%, reaching a total of 583 new CNMs and CMs graduating in 2014 . Despite this progress, the growth of midwifery education programs has not kept pace with the increasing number of qualified applicants, with the most significant limiting factors being the availability of clinical preceptors and training sites . In 2014, ACNM estimates that there were 1600 qualified applications for 1096 spaces, with 88.5% of the unfilled spaces occurring in the 19 programs that only accepted registered nurse (RN) applicants .…”
Section: Introductionmentioning
confidence: 99%
“…Many preceptors desire students with this experience in order to maintain their level of clinical productivity, even in the office setting. Germano et al identified decreased productivity as one of 4 major barriers to precepting midwifery students and found that an inexperienced student can prevent a preceptor from seeing a full caseload . Several strategies exist to facilitate the preceptor‐student relationship and support preceptor productivity, including the concept of quality learning experiences over quantity.…”
Section: Strategies For Midwifery Educationmentioning
confidence: 99%
“…Several strategies exist to facilitate the preceptor‐student relationship and support preceptor productivity, including the concept of quality learning experiences over quantity. Preceptors can select clinical experiences for students that enhance the students’ level of learning while maintaining productivity in their practices . A variation on this idea allows a student and preceptor to see separate clients simultaneously.…”
Section: Strategies For Midwifery Educationmentioning
confidence: 99%
See 1 more Smart Citation